Profile of Ocular Trauma among Patients attending A Regional Referral Hospital in Tanzania (Tanzania Medical Journal, 2023)
BackgroundOcular trauma is a major cause of blindness worldwide. It has an impact on all the aspects of an individual’s life. This study aimed to assess the profile of ocular trauma among patients who attended the eye clinic at Mawenzi Regional Referral Hospital.MethodologyThis was a descriptive retrospective cross-sectional hospital-based study of patients who attended Mawenzi Regional Referral Hospital from 31st August 2017 to 30th August 2019. It included all patients with ocular trauma who attended the hospital during the study period. All case notes of patients who had ocular trauma were retrieved.  A total of 677 patients were attended for ocular trauma between August 2017 and August 2019; in which 329 and 348 patients were attended in first and second year respectively. A predetermined proportion of case files of patients to be included in the study was calculated for each year based on the total number of patients attended in the particular year. Therefore 48 case files were selected for the first year and 51 for the second year making a sample size of 99 case files. Data was analyzed using the Statistical Package for Social Sciences version 20.0.ResultsThe magnitude of ocular trauma in our study was 5.1%. Unilateral eye trauma accounted for 85.9% of all the cases. The mean age was found to be 30 years with ages ranging from 1 to 85 years. The commonest age group affected was 16 to 30 years (35.4%). There was a male to female ratio of 2:1 with males having a higher rate of sustaining ocular injury (66.7%). Majority of the patients presenting at the hospital were from the rural areas (72.7%). Mechanical causes represented the highest percentage of cases (73.7%) with sticks being the commonest agents of injury (26.3%). Closed globe injuries presented more frequently (71.7%). The most common place of sustaining ocular injuries was reported to be at home (29.3%) and at the workplace (27.3%).ConclusionOcular trauma was seen to be of significant magnitude at Mawenzi Regional Referral hospital. A large number of cases resulted from mechanical causes with sticks being the commonest agents. Closed globe injuries were found to be more common than open globe injuries. Most of the ocular trauma cases were sustained at home followed by the workplace.